Influence of grass pellet production on pyrrolizidine alkaloids occurring in Senecio aquaticus-infested grassland. Issue 4 (3rd April 2018) - Gottschalk, Christoph; Ostertag, Johannes; Meyer, Karsten; Gehring, Klaus; Thyssen, Stefan; Gareis, Manfred
ABSTRACT: 1, 2-Dehydro-pyrrolizidine alkaloids (PA) and their N -oxides (PANO) exhibit acute and chronic toxic effects on the liver and other organs and therefore are a hazard for animal and human health. In certain regions of Germany, an increasing spread of Senecio spp. (ragwort) on grassland and farmland areas has been observed during the last years leading to a PA/PANO-contamination of feed and food of animal and plant origin. This project was carried out to elucidate whether the process of grass pellet production applying hot air drying influences the content of PA and PANO. Samples of hay ( n  = 22) and grass pellets ( n  = 28) originated from naturally infested grassland (around 10% and 30% dominance of Senecio aquaticus ) and from a trial plot with around 50% dominance. Grass pellets were prepared from grass originating from exactly the same plots as the hay samples. The samples were analysed by liquid chromatography-tandem mass spectrometry for PA/PANO typically produced by this weed. The results of the study revealed that PA/PANO levels (predominantly sum of senecionine, seneciphylline, erucifoline and their N -oxides) in hay ranged between 2.1 and 12.6 mg kg −1 dry matter in samples with 10% and 30% dominance of S. aquaticus, respectively. Samples from the trial plot (50% dominance) had levels of up to 52.9 mg kg −1 . Notably, the hot air drying process during the production of grass pellets did not lead to a reduction of PA/PANO levels. Instead, the levels in grass pellets with 10% and 30% S. aquaticus ranged from 3.1 to 55.1 mg kg −1 . Grass pellets from the trial plot contained up to 96.8 mg kg −1 . In conclusion, hot air drying and grass pellet production did not affect PA/PANO contents in plant material and therefore, heat-dried products cannot be regarded as safe in view of the toxic potential of 1, 2-dehydro-pyrrolizidine alkaloids.